2010
DOI: 10.1111/j.1365-294x.2010.04759.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in caves: Darwin’s ‘wrecks of ancient life’ in the molecular era

Abstract: Cave animals have historically attracted the attention of evolutionary biologists because of their bizarre 'regressive' characters and convergent evolution. However, understanding of their biogeographic and evolutionary history, including mechanisms of speciation, has remained elusive. In the last decade, molecular data have been obtained for subterranean taxa and their surface relatives, which have allowed some of the classical debates on the evolution of cave fauna to be revisited. Here, we review some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 139 publications
(259 reference statements)
2
168
0
1
Order By: Relevance
“…These experts used their prior knowledge to assign likely species. (4) Molecular data have proven a major innovation in delineation of new species, both cryptic and otherwise (Juan et al 2010). Hence, in situations in which it was uncertain whether there were distinct species present, genetic methods were used to estimate 'known' but undescribed species from recent collections and molecular studies.…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…These experts used their prior knowledge to assign likely species. (4) Molecular data have proven a major innovation in delineation of new species, both cryptic and otherwise (Juan et al 2010). Hence, in situations in which it was uncertain whether there were distinct species present, genetic methods were used to estimate 'known' but undescribed species from recent collections and molecular studies.…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 99%
“…Colonisation of these habitats by multiple unrelated surface species has also contributed to the high levels of diversity (Leys et al 2003;Cooper et al 2008;Guzik et al 2008). Further, in situ speciation within aquifers is also considered a plausible source of species diversity, particularly in the Yilgarn (Guzik et al 2009;Juan et al 2010) and Pilbara (Finston et al 2009). Abiotic heterogeneity within habitats (i.e.…”
Section: The Predicted Origins Of This Diversitymentioning
confidence: 99%
“…In some caves of volcanic origin, hydrogen sulphide can reach concentrations of > 300 μM (Riesch et al 2010). These habitats host a unique fauna (Iliffe and Kornicker 2009;Juan et al 2010) and because they represent independent evolutionary trajectories of adaptations to similar conditions, similar to islands for the terrestrial environment, they are considered one of the most important habitats to study marine island biogeography (Dawson 2016).…”
Section: Submarine Cavesmentioning
confidence: 99%
“…It also has reduced eyes, and a less pigmented body than other Aphaenogaster species. Loss of wings, reduction of eyes, elongation of antennae and legs, and loss of pigmentation are commonly observed in troglobiotic arthropods (Vandel 1964, Christiansen 1965, Culver 1982, Marques & Gnaspini 2001Juan et al 2010). It is unclear whether A. gamagumayaa displays any wing loss/reduction in the queen and male, as during the course of the study only workers were found.…”
Section: Discussionmentioning
confidence: 86%